2021
DOI: 10.3390/ijerph18189571
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Changes among Polish University Students during the COVID-19 Pandemic

Abstract: Students worldwide have been impacted by nationwide safety closures due to the COVID-19 pandemic, creating an environment with loss of interaction with colleagues, social isolation, boredom, and economic uncertainty. Since university students were considered uniquely vulnerable to mental health problems even before the pandemic, this study aimed to investigate lifestyle and behavioral changes experienced by this population due to the epidemiological situation and their effect on their mental health. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 63 publications
(70 reference statements)
4
33
0
3
Order By: Relevance
“…The results of this study confirm, as expected, the high prevalence of insomnia, PTSD, psychopathological symptoms, and psychological distress in the studied population of university students. These are in line with the findings of previous studies reporting a high prevalence of insomnia, anxiety, and depressive symptoms in the population, among other adverse mental health outcomes during the COVID-19 pandemic [2,23,[28][29][30][31][32].…”
Section: Main Findings and Context Of The Researchsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study confirm, as expected, the high prevalence of insomnia, PTSD, psychopathological symptoms, and psychological distress in the studied population of university students. These are in line with the findings of previous studies reporting a high prevalence of insomnia, anxiety, and depressive symptoms in the population, among other adverse mental health outcomes during the COVID-19 pandemic [2,23,[28][29][30][31][32].…”
Section: Main Findings and Context Of The Researchsupporting
confidence: 92%
“…It includes seven items rating sleep onset, sleep maintenance, problem awakening, dissatisfaction with sleep, impairment in quality of life, interference of insomnia with functioning, and distress due to sleep problems. Based on the total scores, insomnia symptoms are graded as follows: absence of insomnia (0-7), subthreshold insomnia (8)(9)(10)(11)(12)(13)(14), moderate insomnia (15)(16)(17)(18)(19)(20)(21), severe insomnia (22)(23)(24)(25)(26)(27)(28) [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies are the time when many students move to different cities, live with roommates, or in dormitories where they often gather and party together. Previous research showed that an increase in the consumption of alcoholic drinks was accompanied by an increase in overall drinking occasions [24,25]. The closure of universities and social gathering sites combined with the onset of online classes could cause a significant decrease in drinking occasions [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tension and stress accounted for 24% of the variance of the PSQI in students [ 23 ]. The COVID-19 pandemic has decreased the mental health and well-being of university students [ 39 , 40 ]. For instance, 50% of 115 first-year university students estimated their mental health to be worse than before the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%